Tools: Stuff: Art - David Kirshner (Footprint)
Between 1890 and 1898 Erik Satie lived at 6 rue Cortot: ‘in a wardrobe’. Satie was a collector […]. After his death his wardrobe was found to contain 84 handkerchiefs besides 12 identical velvet suits and dozens of umbrellas.  Trois morceaux en forme de poire […] three pieces in the form of a pear. The title of a piano piece in seven parts by Erik Satie. Satie composed this piece in response to Debussy's criticism that his works lacked a 'sense of form'. What exactly did Debussy mean by this? Where and what actually was this scene of formlessness?  The first part of the Paper will advance some possible reasoning behind Debussy's comments. Was Debussy questioning Satie's attitude to what Heidegger [in The Origin of the Work of Art] would term the 'thingly' element of the Work of Art, or more precisely – the relationship between 'things' and the 'thing in itself'? Heidegger's contemplation of 'Form' and his writings on 'tools', 'material' and 'art', and the section dealing with the Temple provides an interesting locus in which to discus Debussy's comments. The second section gives some ideas of how I reinterpreted this argument to produce a series of visual works inspired by another of Satie's works, Furniture Music – Musique d' ameublement, a piece of music that was not to be listened to.  Milhaud later recounted: ‘It was no use Satie shouting: “Talk for heaven's sake! Move around! Don't listen!” They kept quiet. They listened. The whole thing went wrong.’